Analisis Dasar Pertimbangan Hakim Dalam Menjatuhkan Pidana Terhadap Pelaku Tindak Pidana Penggelapan - Rosita Ibrahim; Marsanuddin Marsanuddin; Mirwansyah Mirwansyah (Universitas Sang Bumi Ruwa Jurai, 2018)
Perpetrators of embezzlement are usually sentenced to a maximum of four years in accordance with the provisions of Article 372 of the Criminal Code (KUHP). But in the decision Number: 1487 / Pid.B / 2017 / PN.Tjk, the judge actually relieves the sentence by considering that the perpetrator is only a legal subject, this matter has an element of error in person. The problem in this research is whether it is the basis for judges' consideration in imposing criminal acts against perpetrators of criminal acts of embezzlement and what are the obstacles in examining cases of fraud.The research used is a type of normative descriptive legal research, through normative and empirical approaches. The types of data needed in the study include primary and secondary data sourced from primary legal materials, secondary legal materials and tertiary legal materials and analyzed qualitatively.From the results of the discussion, it can be concluded that the judges' basis in imposing crimes against the perpetrators of criminal acts of embezzlement on cases Number: 1487 / Pid.B / 2017 / PN. and examination of evidence, it has been found the legal fact that the defendant has been proven to have committed a crime of embezzling a motorized vehicle, namely in the form of a car. While the obstacles in examining cases of embezzlement are the difficulty of presenting witnesses who know the events of the perpetrators or defendants and proof of the goods in the hands of the perpetrators.